Influence of Long‐Term Application of Manure Type and Bedding on Yield, Protein, Fiber, and Energy Value of Irrigated Feed Barley. (1st January 2015) - Miller, J. J.; Beasley, B. W.; Drury, C. F.; Larney, F. J.; Hao, X.
Abstract : The long‐term effect of land application of manure type (composted [CM] vs. stockpiled [SM] manure), bedding (wood‐chips [WD] vs. straw [ST]), and application rate on yield, protein, fiber, and energy value of feed barley ( Hordeum vulgare L.) for beef cattle ( Bos taurus ) is unknown. Dry matter yield and feed quality of irrigated feed barley was measured on a clay loam soil after 5 (2002), 8 (2005), and 12 yr (2009) of annual applications of CM or SM feedlot manure with WD or ST bedding at three application rates (13, 39, 77 Mg ha −1 dry wt.). The treatments also included an unamended control and inorganic fertilizer treatment. Mean yields in 2005 were significantly ( P ≤ 0.05) greater for CM–ST than SM–WD but CM–ST was similar to SM–ST and CM–WD. Yields in 2009 were significantly lower for CM–WD compared to the other three treatments, and were greater for ST‐13 and WD‐77 compared to WD‐13. Crude protein was greater for SM than CM when averaged over the 3 yr. Bedding influenced crude and soluble protein but the effects depended on interactions with rate and year. For example, crude and soluble protein in 2009 was greater for ST than WD at the 39 and 77 Mg ha −1 rates. Manure type and bedding may be practices to manage feed barley yield and protein, but will likely have little or no effect on the fiber content and energy value of the feed.